2020
DOI: 10.24093/awej/call6.20
|View full text |Cite
|
Sign up to set email alerts
|

Using Pedagogic Video to Enhance English for Specific Purposes Teaching Program (ESP) for Saudi University Students: A New Prospective Approach

Abstract: The optimized use of authentic videos is integral in language classrooms. However, the research concerning the use of videos for developing audiovisual reception, four language skills, and vocabulary are found to be lacking. This study, therefore, reviews the developments related to the use of video in English for Specific Purposes (ESP). The main question of this study is: how does the pedagogic video contribute to improving English learner's language skills? This study is beneficial for university teachers w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The results of the English language test are shown in table (1). Results obtained from data analysis of the questionnaire, as shown in table (2), revealed that most respondents agree that the early learners are better than late ones as appeared from most items responses. For example, in the first item, 70 % agree that the best suitable age to start learning EFL is the age of 5-6, whether 30% do not agree.…”
Section: Resultsmentioning
confidence: 94%
“…The results of the English language test are shown in table (1). Results obtained from data analysis of the questionnaire, as shown in table (2), revealed that most respondents agree that the early learners are better than late ones as appeared from most items responses. For example, in the first item, 70 % agree that the best suitable age to start learning EFL is the age of 5-6, whether 30% do not agree.…”
Section: Resultsmentioning
confidence: 94%
“…Take an example, García-Pinar (2019) reported that The use of TED talks has significantly improved students' learning experiences and is favourably associated with their motivation. Previous studies also reported that making a video project makes students feel confident speaking (Mohammed Alhaj & H. Albahiri, 2020;Radosavlevikj & Hajrullai, 2019) and enhances ESP teaching programs as well (Syafiq et al, 2021). Kusumawati (2020) confirmed that students were required to finish the project based on the knowledge, guidance, and practice that had been done in the previous activity.…”
Section: Introductionmentioning
confidence: 90%
“…Bashir [34] make efforts to improve students' critical thinking skills through discovery learning. As for pedagogical competence, Alhaj and Albahiri [35] makes efforts to increase student pedagogic competence through microteaching techniques, and Çelik et al [36] made efforts to increase student pedagogic competence through apprenticeship techniques.…”
Section: Introductionmentioning
confidence: 99%